If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(2x + 6) = 24 Reorder the terms: 8x + -1(6 + 2x) = 24 8x + (6 * -1 + 2x * -1) = 24 8x + (-6 + -2x) = 24 Reorder the terms: -6 + 8x + -2x = 24 Combine like terms: 8x + -2x = 6x -6 + 6x = 24 Solving -6 + 6x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 24 + 6 6x = 24 + 6 Combine like terms: 24 + 6 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 9x^2+18y^4= | | 66*8= | | 32b^2+12b= | | 3u+(u-2)=10 | | y^2-10y=-23 | | (x-2)5=0 | | (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 | | 3x-7=9+7x | | x+8=-2-x | | 15x^2+2xy-8y^2=0 | | 80x=-280 | | 100x=400 | | 2(x+2)=3(3x-4) | | 23x+10=28x+30 | | 21x+2=21x+11 | | 5-(2x+4)=3-(3x+2) | | x+24=24-y | | 12y^2-19y-21=0 | | x^4+4x=-c | | x^4+4x=c | | 4x+1+4c=5c-3x+6 | | 6y^2+23y+7=0 | | 3y^2-11y+10=0 |